Pengaruh media Crossword Puzzle Online terhadap minat belajar peserta didik pada mata pelajaran Sejarah (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
Low student interest in history learning often leads to limited engagement and reduced learning outcomes. This study aims to analyze the effect of the Crossword Puzzle Online media on students’ interest in learning history. A quantitative approach with a quasi experimental method and a nonequivalent control group design was employed. The sample was selected using purposive sampling, consisting of an experimental class (n = 37) and a control class (n = 34). The learning interest instrument was validated through content and construct validity and demonstrated high reliability (Cronbach’s Alpha = 0.864). Data were analyzed using normality, homogeneity, and hypothesis testing through an independent sample t-test. The results showed a substantial increase in the experimental group’s mean score from 59.57 (pretest) to 70.27 (posttest), while the control group only increased from 60.20 to 61.35. The t-test result indicated a significance value of p < .001 (p < 0.05), confirming that the Crossword Puzzle Online media had a significant effect on students’ learning interest. These findings reveal that digital game-based media can foster student enjoyment, concentration, and active participation during history learning. Therefore, Crossword Puzzle Online is an effective alternative to enhance students’interest and engagement in history classrooms.
Keywords: Crossword puzzle online; history learning; learning interest; student engagement